Transpressional segment boundaries in strike‐slip fault systems offshore southern California: Implications for fluid expulsion and cold seep habitats. Issue 10 (26th May 2015) - Maloney, Jillian M.; Grupe, Benjamin M.; Pasulka, Alexis L.; Dawson, Katherine S.; Case, David H.; Frieder, Christina A.; Levin, Lisa A.; Driscoll, Neal W.
Abstract The importance of tectonics and fluid flow in controlling cold seep habitats has long been appreciated at convergent margins but remains poorly understood in strike‐slip systems. Here we present geophysical, geochemical, and biological data from an active methane seep offshore from Del Mar, California, in the inner California borderlands (ICB). The location of this seep appears controlled by localized transpression associated with a step in the San Diego Trough fault zone and provides an opportunity to examine the interplay between fluid expulsion and restraining step overs along strike‐slip fault systems. These segment boundaries may have important controls on seep locations in the ICB and other margins characterized by strike‐slip faulting (e.g., Greece, Sea of Marmara, and Caribbean). The strike‐slip fault systems offshore southern California appear to have a limited distribution of seep sites compared to a wider distribution at convergent plate boundaries, which may influence seep habitat diversity and connectivity.